Antioxidant status of interval-trained athletes in various sports - Dekany, M.; Nemeskeri, V.; Györe, I.; Harbula, I.; Malomsoki, J.; Pucsok, J. (International Journal of Sports Medicine, 2006)
Muscular exercise results in an increased production of free radicals and other forms of reactive oxygen species (ROS). Further, developing evidence implicates cytotoxins as an underlying etiology of exercise-induced stimuli in muscle redox status, which could result in muscle fatigue and/or injury. Two major classes of endogenous protective mechanisms (enzymatic and nonenzymatic antioxidants) work together to reduce the harmful effects of oxidants in the cell. This study examined the effects of acute physical exercise on the enzymatic antioxidant systems of different athletes and comparison was made to the mechanism of action of three main antioxidant enzymes in the blood. Handball players (n = 6), water-polo players (n = 20), hockey players (n = 22), basketball players (n = 24), and a sedentary control group (n = 10 female and n = 9 male) served as the subjects of this study. The athletes were divided into two groups according to the observed changes of activity of superoxid dismutase enzyme. The antioxidant enzyme systems were characterized by catalase (CAT), gluthation-peroxidase (GPX), and superoxid-dismutase (SOD) and measured by spectrophotometry. An important finding in the present investigation is that when the activities of SOD increased, the activities of GPX and CAT increased also and this finding related to the physical status of interval-trained athletes. Positive correlation between SOD and GPX activities was observed (r = 0.38 females, r = 0.56 males; p < 0.05). We have observed that the changes in the primary antioxidant enzyme systems of athletes are sport specific, and different from control subjects. Presumably, with interval-trained athletes, hydrogen-peroxide is significantly eliminated by gluthatione-peroxidase. From these results it can be concluded that the blood redox status should be taken into consideration when establishing a fitness level for individual athletes.